Vision-based 3D human and hand pose analysis - Cai, Yujun (Nanyang Technological University, 2021)
Vision-based 3D human and hand pose analysis has been a fast-growing research area and has aroused long-standing research attention in the past decades, since it plays a significant role in numerous applications such as human-computer interactions, robotics, and gesture recognition. Despite the great progress in this field, it is still challenging to obtain accurate 3D pose estimation, predict future motions, and synthesize realistic human behaviors due to the physical complexity of human/hand motion and the lack of high-quality dataset. To address these issues, in this thesis, four chapters are proposed to investigate these tasks.